Effectiveness of intra-arterial nimodipine on central retinal artery occlusion - Minh, Le Nguyen Ngoc; Huynh, Le Vu; Hoa, Duong Dang; Quan, Duong Anh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: Central Retinal Artery Occlusion (CRAO) is a rare but severe ophthalmic emergency characterized by sudden, painless vision loss. Standard treatments often have limited success. This study explores the use of intra-arterial nimodipine as a potential treatment for CRAO. Case report: We present a case series of three patients diagnosed with CRAO at Hue Central Hospital. All patients had visual acuity of 1/10 and failed to respond to standard treatments including ocular massage, anterior chamber paracentesis, and hyperbaric oxygen therapy. Intra-arterial nimodipine (20 mg) was administered via the internal carotid artery. Visual acuity was assessed at baseline, immediately after treatment, at 3 days, and 1 month post-treatment. Digital Subtraction Angiography (DSA) images were obtained before and after treatment. All three patients showed immediate improvement in visual acuity following intra-arterial nimodipine treatment, with increases to 4/10 or 5/10. These improvements were sustained at 3 days and 1 month follow-up. DSA images demonstrated notable vasodilation with improved blood flow to the retinal arteries and posterior ciliary artery. The procedure was well-tolerated, with only mild and transient side effects reported. Conclusion: Intra-arterial nimodipine shows promise as a treatment for CRAO, demonstrating significant improvements in visual acuity even after the failure of standard treatments. However, larger, controlled studies with longer follow-up periods are necessary to confirm its efficacy and safety before it can be considered as a standard treatment option.